Impact of walking exercise intensity on cartilage IL-1, TNF-α, IL-4, MMP-13 and pain threshold in osteoarthritis rat models - Handono, Kusworini; Prasetyo, Dwi A.; Kurnianingsih, Nia; Wahono, Cesarius S.; Albaar, Thoha M. (Narra Sains Indonesia, 2025)
Pro-inflammatory cytokines produced by chondrocytes play a crucial role in activating matrix metalloproteinase-13 (MMP-13), leading to an imbalance between the synthesis and degradation of the extracellular matrix (ECM) in osteoarthritis (OA). Although regular walking exercise has been shown to reduce inflammatory cytokine levels in OA animal models, the optimal exercise intensity remains underexplored. Therefore, the aim of this study was to investigate the effects of different intensities of regular walking exercise on the levels of pro-inflammatory cytokines (interleukin-1 (IL-1), tumor necrosis factor-alpha (TNF-α)), anti-inflammatory cytokine (interleukin-4 (IL-4)), as well as MMP-13 expression in cartilage and pain thresholds in an OA animal model. A total of 30 adult male Rattus norvegicus (6–8 weeks old) were divided into five groups: (1) healthy control; (2) monosodium iodoacetate (MIA)-induce OA model; (3) OA with light-intensity walking (OA1); (4) OA with moderate-intensity walking (OA2); (5) and OA with high-intensity walking (OA3). The exercise intervention began one week after MIA injection and continued for six weeks. Pain threshold, inflammatory cytokine (IL-1, TNF-α, IL-4) levels, and MMP-13 expression were measured using an analgesymeter, enzyme-linked immunosorbent assay (ELISA), and immunohistochemistry (IHC), respectively. The results demonstrated a significant reduction in IL-1 and TNF-α levels, along with decreased MMP-13 expression and increased IL-4 levels, in all exercise groups (OA1, OA2, OA3) compared to the untreated OA group. Additionally, pain thresholds improved following exercise. However, no significant differences were observed among the three exercise intensities in terms of cytokine levels, MMP-13 expression, or pain threshold. This study highlights that the light-intensity regular walking exercise effectively reduces inflammation, MMP-13 expression, and pain in OA. Further research is needed to elucidate the underlying mechanisms of exercise in OA management.